Necrotizing pneumonia following cardiac surgery in a neonate - Ruqaiah S. Al Tassan; Sulaiman Al Alola; Hesham Al Shaalan; Suhail Al Saleh (Elsevier, 2013)
Summary: In this report, we discuss the case of a male neonate who underwent surgical correction for coarctation of the aorta. The recovery of this patient was complicated by postsurgical necrotizing pneumonitis that resolved completely after a prolonged hospital stay with recurrent deterioration. Keyword: Necrotizing pneumonia